2014
DOI: 10.2190/om.69.1.f
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Approaches Toward Euthanasia

Abstract: It was concluded that the lack of legal regulations, ethical considerations, religious beliefs, and work experience with dying patients affect nursing students' attitudes towards euthanasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
(25 reference statements)
2
15
0
Order By: Relevance
“…Like our study, others reported a higher general acceptance of euthanasia than a willingness to take an active part in ending a patient's life. 37,38 Another factor related to the attitude towards end-oflife issues were religious beliefs. A high religious affinity to one of the Christian churches among our study participants could be an additional factor contributing to a high level of rejection of euthanasia.…”
Section: Discussion Euthanasiamentioning
confidence: 99%
“…Like our study, others reported a higher general acceptance of euthanasia than a willingness to take an active part in ending a patient's life. 37,38 Another factor related to the attitude towards end-oflife issues were religious beliefs. A high religious affinity to one of the Christian churches among our study participants could be an additional factor contributing to a high level of rejection of euthanasia.…”
Section: Discussion Euthanasiamentioning
confidence: 99%
“…The variation between countries could be largely explained through the differences in religious beliefs and cultural and socio-demographic factors. 43,45,46 Moreover, Islam is one of the most important determining factors in Turkish society's attitude towards euthanasia, which explains the findings. 47 PAS is one of the most difficult challenges for healthcare providers in relation to their primary duty, which is saving lives and treating and caring for patients.…”
Section: Attitudes Of Muslims Towards Physicianassisted Suicide and Ementioning
confidence: 72%
“…To overcome these limitations, a secondary search strategy was performed as follows. The references listed in the 46 selected articles 1,3,5,6,[8][9][10][11][12][13][15][16][17][20][21][22][23][24][25][26]29,30,32,33,36,[40][41][42][43][44]46,[48][49][50][51][52][53][54][55][56][57]59,66,[71][72][73] were checked for further relevant references, and religious books (Quran and hadith) and legal codes of selected countries were also consulted from websites. The secondary search strategy resulted in an additional 30 references, which we included in this review.…”
Section: Methods For Literature Searchmentioning
confidence: 99%
“…Medical students and residents should be familiar with the concepts and principles of medical ethics in view of the finitude of life, as topics such as euthanasia, dysthanasia, terminality and the legalization of euthanasia are central to the reflection of health professionals in work groups, ethics committees and public debates 5 . Several countries such as Poland 5,6 , Pakistan 37 , United States 38 , Turkey 39 , Mexico 40 , England and Belgium 41 have been advancing in this regard and discussing the issue with health students.…”
Section: Medical Education and Curriculum Guidelinesmentioning
confidence: 99%